2012
DOI: 10.1111/j.1467-8535.2012.01338.x
|View full text |Cite
|
Sign up to set email alerts
|

The landscape of educational technology viewed from the ETR&D journal

Abstract: The purpose of this study was to conduct a citation network analysis of Educational Technology Research and Development (ETR&D) to examine the trends and issues of the educational technology field's scholarly community that have evolved in the past two decades. The distinctive features of citation network analysis used in this study derive from a social network analysis approach to see relational and network patterns in the citation data. From this citation network analysis, we obtained the following results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 89 publications
0
13
0
Order By: Relevance
“…While this constitutes a contemporary selection of publications, the relative low proportion of articles younger than two years indicates that not all of the latest developments might be represented in the visualization. However, in a comparable co-citation mapping effort in educational technology by Cho et al (2012), the mean age of papers was 14.1 years (Median = 14 years) which is almost double the age of publications in the co-readership analysis. In addition, only 18% of the 28 papers included in the co-citation analysis were less than 10 19 Calculation based on the exact date of data collection on 10/08/2012 This suggests that the results of a co-readership analysis may be much more up-to-date than co-citation analysis.…”
Section: Recencymentioning
confidence: 86%
“…While this constitutes a contemporary selection of publications, the relative low proportion of articles younger than two years indicates that not all of the latest developments might be represented in the visualization. However, in a comparable co-citation mapping effort in educational technology by Cho et al (2012), the mean age of papers was 14.1 years (Median = 14 years) which is almost double the age of publications in the co-readership analysis. In addition, only 18% of the 28 papers included in the co-citation analysis were less than 10 19 Calculation based on the exact date of data collection on 10/08/2012 This suggests that the results of a co-readership analysis may be much more up-to-date than co-citation analysis.…”
Section: Recencymentioning
confidence: 86%
“…Cho et al, 2011) and educational technology (Y. Cho et al, 2013). More recently, Hedayati et al (2017) identified disciplines that have contributed to contemporary HRD research through citation analysis of articles published in HRDQ from 2007 to 2013.…”
Section: Citation Analysis Of Hrdmentioning
confidence: 99%
“…Learning environments are extensively covered, but personal learning environments are not mentioned as a newer development in this area. Communities of practice are not considered, with the exception of situated learning mentioned by Cho et al (2012). Finally, there are areas related to the teacher's perspective of educational technology in the co-citation analyses discussed, but the framework of technological pedagogical content knowledge is not reflected in any of them.…”
Section: Areas Only Present In the Co-readership Visualizationmentioning
confidence: 99%